Unique Responses of Hepatocellular Carcinoma and Cholangiocarcinoma Cell Lines toward Cantharidin and Norcantharidin - Ma, Qixiang (J Cancer, 2018)
The present study aimed to investigate whether cell lines from human gastric and liver cancers respond differently toward cantharidin (CTD) and norcantharidin (NCTD) than other types of cancer cells. We first established the half maximal inhibitory concentrations (IC50s) of CTD for a large panel of cancer cell lines representing the 12 major types of human cancers and the mode of cell death induced by the two compounds. We next compared the growth inhibitory effects as well as the corresponding modes of action of CTD and NCTD. The IncuCyte ZOOM system was used as a semi-high throughput means to define IC50s and 90% inhibitory doses (IC90s) as a reference for the maximal tolerable doses (MTDs) for the two compounds in 72 cancer cell lines. Classical clonogenic survival assay was used to assess the anti-proliferative effect of CTD on selected cell lines of interest. In addition, DNA content-based flow was used to interrogate the modes of cell death following CTD or NCTD exposure. The results of these experiments led to several findings. 1). Cell lines representing hepatocellular carcinomas (HCCs) and cholangiocarcinomas (CCs) were among the most sensitive toward CTD, consistent with the previous clinical study of this compound and its source of origin, Mylabris. 2). Among the individual cell lines of a given cancer types, the sensitivity trends for CTD and NCTD did not exhibit a good correlation. 3) CTD and NCTD caused distinctive cytotoxic effects on HepG2 cells. Specifically, while a cytostatic effect is the primary cause of growth inhibition of CTD, cytotoxic effect is the main contributing factor for the growth inhibition of NTCD. These results indicate that liver cancer cell lines are among the most sensitive to CTD and that CTD and NCTD exhibit their effects through distinct mechanisms.